CLASSIFICATION OF INTERROGATIVE SENTENCES IN LINGUISTICS AND THE ROLE OF DUBITATIVE INTERROGATIVE SENTENCES - Ochilova Akramovna, Khabiba (THE INNOVATION ECONOMY, 2025)
The article analyzes the classification of interrogative sentences in linguistics and their various forms, including the role of interrogative sentences. Interrogative sentences were divided into general, special, selection and confirmatory questions, and the linguistic features and communicative functions of each type were considered. The article examines suspicious interrogative sentences separately and highlights their role in expressing semantic uncertainty, suspicion and probability. The morphological and syntactic forms of suspicious interrogative sentences are given in detail, as well as the features that distinguish them from other types of interrogative sentences. The article also examined the use of dubious interrogative sentences in different languages, which serves to determine their place in general linguistics.